An Analysis of The Students Preposition Errors in Writing Recount Text at English Department in Academic Year 2013/2014 at IAIN Imam Bonjol Padang - Vivi Zurniati (International Journal of Educational Dynamics, 2019)
Preposition is one of language elements that plays an important role to join the words to build sentences. However, the errors of using it keep occurring in the sixth semester students writing compositions. This research was conducted to find out and analyzed the errors on using preposition that occur in the students writing of recount essay. This research was classified into descriptive one. This research was about the errors of preposition used in the recount essay done by the sixth semester students of English Department of IAIN Imam Bonjol Padang. The data of this research were the incorrect preposition found in the recount essay written by the students. The data were collected through giving the students a writing test of recount test. In order to know the causes of the errors, the data were collected by doing the interview. This research investigated about the types of errors and which type that mostly occurs of preposition used in the writing of recount essay and what are the causes. The findings show that the students made some errors on the use of preposition. They are within the category of interlingual; features of L1 are transferred to the target language, and intralingual; ommission, addition, misselection of FL preposition, and redundancy. These types are based on Corder. Meanwhile, the interview guideline is derived from Richards theory of causes of errors. The cause of error in using English preposition is the ignorance of the rule restriction that the students perform in doing the writing activity. To conclude, the error in using English preposition is because of the students low of grammatical ability.